Preliminary Application of a Low-cost Smart Collar Developed for Wild Animal Tracking - İmamoğlu, Ahmet Furkan; Taş, İnanç (Forest Engineering and Technologies Platform, 2022)
Global Positioning System (GPS) technology has been used in many different fields for many years. In recent years, GPS technologies have started to be preferred along with telemetry method in the monitoring and tracking of wild animal. This technology has been widely used especially in developing collars for wild animal tracking. However, due to the high cost of such devices and limited user intervention, they are not commonly used by practitioners or researchers with limited budget. Today, many hardware-based platforms have been developed with the developing technology. The Arduino platform, one of the prominent ones with its technical features, has great advantages of having different sensors and hardware work on single device. Besides, it is possible to produce cost-effective devices using this platform. Within the scope of this study, an Arduino-based wild animal tracking device (FiT-SMART Collar 2.0) with GPS support and remote data transfer via GSM was produced. The produced device was preliminary tested with a vehicle in the city traffic of Bursa, Türkiye. According to the results, the accuracy of the tracking data provided by smart collar was within the acceptable range of 2-3 m. Besides, instant tracking data has been successfully received in the system application using the GSM data transfer system attached on the platform.
Keywords: Engineering; Mühendislik